The Relationship Between and Correlates of Problematic Sexual Behavior and Major Mental Illness - Moulden, Heather M.; Myers, Casey; Lori, Anastasia; Chaimowitz, Gary (Frontiers in Psychology, 2022)
While research has consistently found that general distress and psychopathology are not predictive of sexual recidivism, examination of specific syndromes and their relationship to offending has revealed a potentially more complicated relationship. One proposed mechanism for the mixed findings with respect to major mental illness and sexual offending may be the confound of neurological injury. As identified in Mann, Hanson and Thornton’s (2010) work on psychologically meaningful risk factors, mental illness represents an area in need of more study given the indirect influence it may exert on risk. To this end, the current paper summarizes the study of the relationship between neurological injury, psychosis and problematic sexual behaviour among two Canadian samples of forensic and civil psychiatric patients. In the first study we observed higher than expected rates of sexually-themed psychotic symptoms (45%) and problematic sexual behaviour (PSB; 40%) among a combined group of forensic and civil psychiatric patients (n = 109). Indeed 70 percent of those individuals who engaged in PSB endorsed sexually-themed psychotic symptoms. While comorbidity is common amongst this group, brain injury appeared to represent a specific liability. Compared to those who did not engage in PSB, those who did were almost 4x (OR = 3.83) more likely to have a documented history of brain injury (e.g. traumatic and acquired brain injury, including fetal alcohol syndrome). In the second study we sought to replicate this finding in a larger forensic sample of 1,240. However, the recorded rates of brain injury were significantly less, such that no relationship to PSB was observed. Based on the mixed findings to date, including our own data, questions remain about the nature of a potential shared vulnerability for psychosis and PSB previously postulated. Among psychiatrically complex individuals who engage in PSB, understanding etiology and links to risk are helpful, but perhaps more importantly is attention to the mechanisms through which symptoms confer risk (e.g. problem solving, sexual disinhibition, social/intimacy deficits) and how best to treat and manage them.